Participatory Beach Clean-Up Program to Support Sustainable Ecotourism at Kolam Bebek Tourist Beach, Nagan Raya - Mitfhahul Rizqi; Sri Wahyuni; Asri Mursawal; Hayatun Nufus; Ika Kusumawati; Mai Suriani; Mohamad Gazali; Arung Samudra; Hendri Kurniawan (Mitra Akademia Indonesia, 2026)
Coastal tourism areas are increasingly challenged by marine litter, particularly plastic waste, which threatens environmental quality and reduces the attractiveness of tourist destinations. This issue is also evident at Kolam Bebek Tourist Beach in Kuala Trang Village, Nagan Raya Regency, Aceh, where a sustainable community-based waste management system has not yet been established. This community service program aimed to enhance environmental awareness among local communities and visitors, encourage stakeholder participation in beach clean-up activities, and provide supporting facilities for proper waste management. The program was conducted on 28 June 2026 using a participatory approach involving lecturers and students from the Marine Science Study Program of Universitas Teuku Umar, local residents, tourism managers, and the village government. The implementation consisted of four stages: preparation, environmental education and socialisation, beach clean-up activities, and the provision of waste management facilities and educational media, including waste bins and environmental awareness banners. The program successfully reduced waste accumulation along the coastal area, with plastic waste identified as the dominant type of debris collected. Educational activities improved participants' understanding of the environmental impacts of marine litter and the importance of waste segregation. Furthermore, the installation of waste disposal facilities encouraged responsible waste disposal practices among visitors and the local community. Collaboration among academic institutions, local communities, tourism managers, and village authorities strengthened collective commitment to maintaining environmental cleanliness and supporting sustainable coastal tourism. The program demonstrates that participatory environmental education combined with practical action and supporting infrastructure is an effective strategy for improving coastal waste management and can serve as a model for other coastal tourism destinations.